2005
DOI: 10.1017/s0952675705000643
|View full text |Cite
|
Sign up to set email alerts
|

The origin of vowel-length neutralisation in vocoid sequences: evidence from Finnish speakers

Abstract: A number of languages have independently developed a pattern of vowel-length neutralisation according to which a vowel after a vocoid must be long. It is proposed that this pattern arises from the inherent acoustic ambiguity of such sequences, which are realised with a diphthongal transition from one formant pattern to the next, with no clear boundary between the two. Neutralisation in vocoid sequences originates from listeners' difficulties in determining the duration of vowels in this context. Lengthening of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…The next experiment was designed to specifically test the effect of such variation in formant duration on the perception of length in glides. Myers & Hansen (2005) presented Finnish-speaking listeners with stimuli including a glidevowel sequence in which the vowel formant steady state and the glide-vowel formant transition varied in duration. Subjects had the task of identifying the vowel as short or long.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next experiment was designed to specifically test the effect of such variation in formant duration on the perception of length in glides. Myers & Hansen (2005) presented Finnish-speaking listeners with stimuli including a glidevowel sequence in which the vowel formant steady state and the glide-vowel formant transition varied in duration. Subjects had the task of identifying the vowel as short or long.…”
Section: Resultsmentioning
confidence: 99%
“…Myers & Hansen (2005) found that long vowels have longer formant transitions than short vowels in Finnish, and it would be reasonable to expect a similar difference between long and short consonants.…”
Section: Effects Of Consonant Lengthmentioning
confidence: 91%
“…What is the phonetic basis of vowel length neutralization (2b)? Context sensitive neutralizations are associated with multiple phonetic factors: lengthening due to long transitions in pre-vocoid position; shortening in closed syllables; and shortening via devoicing word-finally (Myers & Hansen 2005. Context free mergers are harder to pin down.…”
Section: Banoni Vowel Length Mergermentioning
confidence: 99%
“…The logic goes as follows: sonorants have blurry transitions into and out of flanking vowels, because sonorants are spectrally continuous with surrounding vowels. It is thus hard to pin down where sonorants begin and where they end (Myers & Hansen, 2005;Turk et al, 2006). As a result, their constriction durations are hard to perceive.…”
Section: The Hypothesismentioning
confidence: 99%
“…[iyyi]), it is conceivable that the first part of the geminate can be confused as a part of a preceding (long) vowel (cf. Myers & Hansen 2005). Also concerning rhotic geminates, it would be impossible to prolong the duration of a tap or a flap, and they would instead have to turn into a trill, in order to become a geminate while keeping its rhoticity.…”
Section: Some Caveatsmentioning
confidence: 99%